1968
DOI: 10.4141/cjss68-013
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF VARIOUS ANIONS ON MANGANESE TOXICITY IN SOLANUM TUBEROSUM

Abstract: Potatoes (Solanznn tuberosum L.) were glown on a soil with a pH of 4'5 and containing 12 ppm of exchangeable manganese, and in sand cultures where the manganese concentration ranfed from 02 to 10 ppm. Potassium was sgnplied in the forms of chloride, sulfate, carbonate, nitratc and hydroxide. On unlimed soils, the yields of tubers were in the following order: K,CO, > K-gtI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

1970
1970
2004
2004

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
0
3
1
Order By: Relevance
“…With potatoes we are particularly interested in the uptake and plant Enhanced uptake of Mn under high soil P has been demonstrated by several workers (3,4), particularly when Mn is deficient. This contrasts however, with reports of a beneficial effect of P on the incidence of Mn toxicity in potatoes (2,5). Our own field studies (Peterson and Marsh, in preparation) have shown high Mn uptake, but low Mn toxicity under high P. The present study reports on further investigations into this effect of phosphate.…”
Section: Introductioncontrasting
confidence: 83%
“…With potatoes we are particularly interested in the uptake and plant Enhanced uptake of Mn under high soil P has been demonstrated by several workers (3,4), particularly when Mn is deficient. This contrasts however, with reports of a beneficial effect of P on the incidence of Mn toxicity in potatoes (2,5). Our own field studies (Peterson and Marsh, in preparation) have shown high Mn uptake, but low Mn toxicity under high P. The present study reports on further investigations into this effect of phosphate.…”
Section: Introductioncontrasting
confidence: 83%
“…The majority of the experimental observations indicate that the Cl-effect is observed in acidic soils (Foy, 1964;Hamilton, 1966;Cheng and Ouellette, 1968), and since liming has been shown to reduce the differential effects of the anions on Mn uptake by plants (Jackson, Westermann, and Moore, 1966), it would appear that the Cleffect is dependent upon the initial soil pH. In weakly acidic and neutral soils, the salt-associated pH decrease may not be great enough to facilitate the Mn oxide reduction by Cl-.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in Ca levels associated with the higher Mn treatments has also been observed in ornamentals (Coorts 1958 Similarly, Parberry (1943) Cheng and Ouellette (1968) Berger and Gerloff (1947a) …”
mentioning
confidence: 94%